2023
DOI: 10.1038/s41467-023-36967-2
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic switch controls an alternative NR2F2 isoform that unleashes a metastatic program in melanoma

Abstract: Metastatic melanoma develops once transformed melanocytic cells begin to de-differentiate into migratory and invasive melanoma cells with neural crest cell (NCC)-like and epithelial-to-mesenchymal transition (EMT)-like features. However, it is still unclear how transformed melanocytes assume a metastatic melanoma cell state. Here, we define DNA methylation changes that accompany metastatic progression in melanoma patients and discover Nuclear Receptor Subfamily 2 Group F, Member 2 – isoform 2 (NR2F2-Iso2) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…However, aberrant overexpression of NRF2 increases antioxidant responses and changes the cellular redox state, aiding in melanoma cell survival, growth, and metastasis [70]. According to a recent study by Davalos et al, Nuclear Receptor Subfamily 2 Group F, Member 2-isoform 2 (NRF2F2-Iso2) promotes the progression of metastatic melanoma by influencing the activity of full-length NR2F2 on neural crest cell (NCC) and epithelial-tomesenchymal transition (EMT) target genes [71]. Importantly, NRF2 may promote invasion and migration by upregulating HO-1 [72].…”
Section: Oxidative Stress In Melanomagenesismentioning
confidence: 99%
“…However, aberrant overexpression of NRF2 increases antioxidant responses and changes the cellular redox state, aiding in melanoma cell survival, growth, and metastasis [70]. According to a recent study by Davalos et al, Nuclear Receptor Subfamily 2 Group F, Member 2-isoform 2 (NRF2F2-Iso2) promotes the progression of metastatic melanoma by influencing the activity of full-length NR2F2 on neural crest cell (NCC) and epithelial-tomesenchymal transition (EMT) target genes [71]. Importantly, NRF2 may promote invasion and migration by upregulating HO-1 [72].…”
Section: Oxidative Stress In Melanomagenesismentioning
confidence: 99%
“…This aberrant DNA methylation in cancer cells enhances cellular plasticity and promotes adaptability and resistance to treatments ( 43 ). Davalos et al ( 44 ) reported that DNA methylation changes accompany the metastasis of melanoma, and nuclear receptor subfamily 2 group F, member 2 isoform (NR2F2-Iso2) is a transfer-driven factor involved in epigenetic regulation. Neural crest cells (NCCs) differentiate into melanocytes upon the inhibition of NR2F2-Iso2 expression via DNA methylation, whereas NR2F2-Iso2 is increasingly hypomethylated and re-expressed in metastatic melanoma.…”
Section: Role Of Transcriptional Regulation Of Mrna In Cancer Cell Pl...mentioning
confidence: 99%
“…Neural crest cells (NCCs) differentiate into melanocytes upon the inhibition of NR2F2-Iso2 expression via DNA methylation, whereas NR2F2-Iso2 is increasingly hypomethylated and re-expressed in metastatic melanoma. Therefore, it was indicated that DNA methylation changes allow transformed melanocytes to acquire NCC- and EMT-like features by controlling NR2F2 activity ( 44 ). In addition, Mancini et al ( 45 ) revealed that the deregulation of DNMTs and several microRNAs (miRNAs) has a relevant role in EMT of prostate cancer cells.…”
Section: Role Of Transcriptional Regulation Of Mrna In Cancer Cell Pl...mentioning
confidence: 99%